Measuring Teacher Engagement: Development of the Engaged Teachers Scale (ETS) - Klassen, Robert M.; Yerdelen, Sündüs; Durksen, Tracy L (Frontline Learning Research, 2013)
The goal of this study was to create and validate a brief multi-dimension scale of teacher engagement—the Engaged Teachers Scale (ETS)—that reflects the particular characteristics of teachers’ work in schools. We collected data from four separate samples of teachers (total N = 823), and followed five steps in developing and validating the ETS. The result of our five steps of analysis was a 16-item, 4-factor scale of teacher engagement that shows evidence of reliability, validity, and usability for further research. The four factors of the ETS consist of: cognitive engagement, emotional engagement, social engagement: students, and social engagement: colleagues. The ETS was found to correlate positively with a frequently used work engagement measure (the UWES) and to be positively related to, but empirically distinct, from a measure of teachers’ self-efficacy. Our key contribution to the measurement of teacher engagement is the novel inclusion of social engagement with students as a key component of overall engagement at work for teachers. We propose that social engagement should be considered in future iterations of work engagement measures in a range of settings.